Increasing Learners' Motivation and Mathematic Learning Outcomes With Contextual Teaching and Learning Approaches for Students at Grade V SD Negeri 07 Tiumang, Dharmasraya Regency - Miyato Miyato (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2022)
The problem behind this research is the many benefits of studying mathematics in solving math problems itself, problems in other subjects, and problems in everyday life so that this study aims to make teachers able to innovate optimally to grow and increase motivation to learn mathematics in elementary school students. 07 Tiumang using Contextual Teaching and Learning Approach.This type of research is Classroom Action Research (CAR) Collaborative Pattern using the Kemmis and Mc cycle model. Taggart which consists of 2 cycles, each cycle consists of 2 meetings. The research subjects were the fourth grade students of SD Negeri 07 Tiumang as many as 22 students. The research instrument has been tested for validity using Expert Judgment & Product Moment Correlation and then tested for reliability using Alpha Cronbach. The data analysis technique used is descriptive qualitative and quantitative.The results showed that in the first cycle students' learning motivation in the sufficient category was 58.1% and an increase in the second cycle in the good category was 74.4%. The average value of students in the first cycle is 59 with a learning mastery value of 63.15% then an increase in the second cycle with an average student score of 68.95 with a learning mastery value is 89.47%. The conclusion of this study is that the contextual teaching and learning approach to flat-shaped material for students at SD Negeri 07 Tiumang can increase student motivation and learning outcomes.